MENUMBUHKEMBANGKAN SIKAP TOLERANSI BEDA AGAMA TERHADAP PESERTA DIDIK DI SEKOLAH - Imam Machali; Itsna Fitria Rahmah (Istitut Ilmu Al-Qur'an (IIQ) An-Nur Yogyakarta Komplek PP An Nur Ngrukem PO BOX 135 Bantul 55702 Yogyakarta Tlp/Fax (0274) 6469012. http://jurnalannur.ac.id/, 2012)
The position of religious education according to the National Education Law, serves to prepare students to be member people who understand and practice the values of their religion and / or a theologian. Indonesia is a country that democratic, but many social conflicts associated with religion. School under the general non religious and religious foundations have an opportunity large to make the experimentation of religious education, one of which could be a response to a multicultural society. SMA BOPKRI 1 Yogyakarta is not using the separation of students at religious instruction, because the school is under the auspices of the Christian foundation doesn’t provide Protestant religious instruction, the other hand religoius education is the answer of this problem.